International partnership at tourist services market - Mazur, Volodymyr (Human Geography Journal, 2017)
The article deals with the following levels of realization of stages of the development of forms of international economic relations: international economic interaction, international economic contacts, international economic cooperation and international economic integration. Publications of modern scholars – investigators of issues of forming and development of partnership relations and the aspects of partnership in international relations.They made a great contribution in the definition of the importance and actuality of the similar way of realization of economic activity and investigation of the forms of its usage. However, it is necessary to emphasize that there is the difference of opinions of scientists concerning theoretical base of forming of partnership relations. The considerable quantity of scientific works was dedicated to the investigation of partnership relations of enterprises with commercial banks, state institutions on the level of foreign economic activity of economic subjects. The development of tourism in Ukraine has been investigated as creating of favorable organizational and legal and economic surrounding of the development to of the sphere, forming competitiveness at the world market of national tourist product on the base of the use of natural and historical and cultural potential of Ukraine and support of its social and economic interests and economic security.